What Chinese Workers Value: An Analysis of Job Satisfaction, Job Expectations, and Labor Turnover in China - Peng Nie; Alfonso Sousa-Poza (Institute of Labor Economics (IZA), 2017)
This study uses data from the 2012 China Labor Force Dynamics Survey and 2010–2012 China Family Panel Studies to investigate job satisfaction and job expectations, as well as the association between job satisfaction and job turnover by gender among employees aged 16–65. We find not only that job satisfaction levels are relatively low, with only 46% of workers explicitly satisfied, but also that worker expectations differ significantly from what their jobs actually provide. In particular, many jobs are less interesting than expected, which prevents workers from realizing their perceived potential. This expectation gap is thus a strong determinant of job satisfaction. Men and women have similar levels of job satisfaction, yet based on observables, one would expect women's job satisfaction to be lower than it actually is, thereby lending support to the gender-job-satisfaction paradox encountered in Western studies. In contrast to Western research, we find no link between job satisfaction and job change, an observation we attribute to China's unique Confucian-based work ethic.
Keywords: J16; J17; J28; 330; ob satisfaction; gender; labor turnover; China